Methodologies used for testing the sealability of endodontic temporary fillings in vitro: A narrative review - Abdul Rahman MF ABDIN; Mouhammad H AL-TAYYAN (Elsevier, 2023)
Introduction: The ability of the temporary filling to seal endodontic access cavities may be crucial for the success of endodontic treatment. Numerous in vitro studies have investigated the sealability of the temporary fillings used in endodontic treatments. However, in vitro sealability studies have been criticized for their inconsistent results and questionable clinical relevance. Some journals have imposed moratoriums on publishing such studies to encourage researchers to test their validity and clinical relevance. Since the implementation of this moratorium, little progress has been made in this field. To further encourage researchers to investigate the reliability of these studies, this review presents an overview of the methodologies of studies that examine the ability of temporary filling materials to seal the endodontic access cavity in vitro and discusses the criticisms of these studies in detail. Materials and Methods: PubMed, Scopus, and Embase electronic databases were searched to identify studies that tested in vitro the ability of temporary filling materials to seal endodontic access cavities. Only original articles published in English between 01/01/1970 and 28/02/2022 were included. Results: The search yielded 551 results. After removing duplicates and excluding studies that did not meet the inclusion criteria, 94 studies were included in this review. Conclusion: Although clinical studies may be the best way to test the performance of temporary fillings, the ethical importance of conducting preliminary in vitro studies is undeniable. It seems that questioning the reliability of in vitro sealability studies is not based on sufficient scientific evidence and that the inconsistencies in the results of these studies may be due to differences in the methodological and clinically relevant variables between them, rather than due to their unreliability.